KINSHIP LANDSCAPE IN THE IMMACULATE CONCEPTION OF LA CAÑADA PARISH (PROVINCE OF MARACAIBO) AT THE END OF THE 18TH CENTURY AND THE BEGINNING OF THE 19TH CENTURY - Rincón Rubio, Luis (2018)
The aim of this article was to contribute to the knowledge of the society of the former Province of Maracaibo, by studying the material culture in the rural parish La Inmaculada Concepción de La Cañada at the end of the 18th century and the beginning of the 19th century, at the scale of the kinship landscape. Understanding material culture in a broad sense as the tangible expression of culture, active in creating meaning and in the constitution of social relations, we investigated the role that the predominant family system in the parish could have played in the construction of the local landscape as a socially produced, inhabited and meaningful space. The probable existence of numerous geographically localized groups of houses with households related by consanguine kinship was identified. These localized kinship groups would have been a materialization of a segment of the own cognatic kinship on the landscape of the parish, constituting a place with meaning, with practical implications from the point of view of social exchange and social cohesion in the parish.